Comparative analysis of package managers Flatpak and Snap used for open-source software distribution - Grzegorz Jan Cichocki; Sławomir Wojciech Przyłucki (Journal of Computer Sciences Institute)
This article presents the result of a research of the Flatpak and Snap package managers used to distribute open-source software on Linux systems. Both package managers are characterised by their versatility and implementation of sandboxing. As part of the research, a test application was prepared, which was built in the Flatpak and Snap formats and published in the official software repositories, where for Flatpak it is Flathub and for Snap it is the Snap Store. The prepared application was first used to test and compare the implementation of sandboxing rules. This was followed by tests of RAM usage and start-up time by the application installed in both formats. The result of the research is an analysis of the measurement results and the drawing of conclusions.